Progressive Muscle Relaxation (PMR) in Cancer Patients: A Scoping Review - Kadek Dwi Pitriyani; Made Deisyana Winaryanta; Luh Mutiara Widiarini; Ni Kadek Mawar Aries Sunday; Komang Agus Jerry Widyanata; Gaviota Khalish; Made Satya Nugraha Gautama (Bali Medical and Wellness Journal, 2025)
Background: Cancer patients frequently endure a range of physical and psychological burdens during treatment. Progressive Muscle Relaxation (PMR) is utilized as a supportive intervention to address these symptoms, though its specific implementation and efficacy require synthesis. Objective: This scoping review aims to investigate the implementation strategies and the effects of PMR on physical and psychological outcomes in patients diagnosed with cancer. Methods: Following PRISMA and Joanna Briggs Institute (JBI) guidelines, a comprehensive literature search was conducted for articles published between 2019 and 2024. Inclusion criteria required studies to be in English or Indonesian and utilize specific designs, including quasi-experimental and randomized controlled trials (RCTs). Results: From a total of 792 initial records, 15 studies met the inclusion criteria. These studies, conducted across various countries, typically utilized PMR interventions lasting 15–25 minutes. The analysis indicated that PMR was associated with reductions in physical symptoms, such as pain, fatigue, nausea, vomiting, and dyspnea. Furthermore, significant improvements were noted in psychological symptoms, including anxiety, stress, and emotional distress, alongside positive effects on sleep quality, functional well-being, coping mechanisms, and resilience. Conclusion: PMR shows promise as a beneficial intervention for alleviating symptom burden in cancer patients. However, the limited number of studies and methodological heterogeneity suggest a need for further rigorous research to clarify the mechanisms of action and expand its clinical applications.